Nominal Group Technique Application Towards the Formation of A Orang Asli Tok Batin Muslim Spiritual Leadership Model - Marlon Pontino Guleng; Halim Mokhtar; Abdul Haiy Mahmod; Zulkefli Aini; Mustafa Kamal Amat Misra (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2023)
This article discusses the Nominal Group Technique (NGT) as an alternative strategy for developing a list of elements for the spiritual leadership model of Tok Batin Muslim. This serves as an alternative to address the shortcomings and enhance the leadership structure of the current indigenous people. The technique has been applied by researchers to construct a list of key elements in the spiritual leadership model of Tok Batin Muslim during the development phase through expert consensus in identifying and accepting the content elements of the model. The study finding shows the total scores for the leadership philosophy component obtained from respondents' views through the survey questionnaire, which is 72 with a percentage value of 93.5%. The total score for the general principles component is 70 with a percentage of 90.9%. The total score for the leadership dimension of al-Qalb is 72 with a percentage of 93.5%. The total score for the leadership dimension of al-aql is 71 with a percentage of 92.2%. The total score for the leadership dimension of nafs is 71 with a percentage of 92.2%, while the total score for the leadership dimension of external behavior is 71 with a percentage of 92.2%. Furthermore, the research findings indicate that the NGT technique has assisted researchers in quickly and easily validating elements because these elements were developed through literature review, subsequent discussions, and expert consensus. The application of the NGT technique also adds diversity to research methods in Malaysia, particularly in the field of indigenous studies.Artikel ini membahas Teknik Kelompok Nominal (NGT) sebagai strategi alternatif untuk mengembangkan daftar elemen untuk model kepemimpinan spiritual Tok Batin Muslim. Ini berfungsi sebagai alternatif untuk mengatasi kekurangan dan meningkatkan struktur kepemimpinan masyarakat adat saat ini. Teknik ini telah diterapkan oleh para peneliti untuk menyusun daftar elemen kunci dalam model kepemimpinan spiritual Tok Batin Orang Asli Muslim selama fase pengembangan melalui konsensus pakar dalam mengidentifikasi dan menerima elemen-elemen kontennya. Temuan penelitian menunjukkan skor total untuk komponen filsafat kepemimpinan yang diperoleh dari pandangan responden melalui kuesioner survei adalah 72 dengan nilai persentase sebesar 93,5%. Skor total untuk komponen prinsip-prinsip umum adalah 70 dengan persentase sebesar 90,9%. Skor total untuk dimensi kepemimpinan al-Qalb adalah 72 dengan persentase sebesar 93,5%. Skor total untuk dimensi kepemimpinan al-aql adalah 71 dengan persentase sebesar 92,2%. Skor total untuk dimensi kepemimpinan nafs adalah 71 dengan persentase sebesar 92,2%, sementara skor total untuk dimensi kepemimpinan perilaku eksternal adalah 71 dengan persentase sebesar 92,2%. Selain itu, temuan penelitian menunjukkan bahwa teknik NGT telah membantu para peneliti dengan cepat dan mudah memvalidasi elemen-elemen karena elemen-elemen ini dikembangkan melalui tinjauan literatur, diskusi selanjutnya, dan konsensus pakar. Penerapan teknik NGT juga menambah keragaman dalam metode penelitian di Malaysia, khususnya dalam bidang studi pribumi.